Exploration of Problem- Based Learning in Hadramout University College of Medicine (HUCOM) - Batarfi, Ali Mohammed (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Problem-based learning is becoming increasingly adopted in universities of higher education throughout the world.Objective: This study is carried out to evaluate the application of this innovative approach in teaching in Hadramout University College of Medicine (HUCOM) in Yemen.Methods: A cross-sectional study was designed to collect data from students through a well structured questionnaire. Students were classified into two groups: students in preclinicalphase (1-3 levels) and students in clinical phase (4-6 level). Results: Out of 372 students participated in the study; 19% in the preclinical phase know about PBL before joining the college while only 16% of students in clinical phase. About 44%students in preclinical phase and 46% of students in clinical phase used all methods for explanation of their learning objectives. A higher percentage of students in preclinical phase(72%) reported that they use library as a source for self-directed learning (SDL) while only 60% of students in clinical phase did.Conclusion: Increased awareness and satisfaction of students toward PBL over time.